(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
This article investigates the economic activity of Pornhub, the most popular pornographic website in the world. First of all, we will explore the business model developed by Pornhub, with the aim of highlighting its main innovative features in the context of the contemporary adult entertainment industry. Secondly, we will pay specific attention to the communication and branding strategies employed by the site in order to develop a “normal” and, above all, responsible business image.